Analisis Faktor-Faktor yang Mempengaruhi Minimnya Kehadiran Pemuda Remaja dalam Mengikuti Ibadah Penelaahan Alkitab (PA) di GKPPD Mungkur Kecamatan Siempat Rube Kabupaten Pakpak Bharat - Delima Padang; Bernhardt Siburian; Herdiana Sihombing; Warseto Freddy Sihombing; Nurelni Limbong (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The purpose of this study was to determine and analyze the factors that influence the low attendance of young people in attending Bible study services (PA) at GKPPD Mungkur, Siempat Rube District, Pakpak Bharat Regency. The research method used is qualitative research. The informant determination technique is data collection with certain considerations. The considerations in question are people who can provide information as expected by the researcher based on certain criteria that are in accordance with the research topic, in this case the researcher interviewed 12 young people from GKPPD Mungkur, Siempat Rube District. The data collection technique for this study is to use interviews and documentation in the form of images. Based on the results of the research that has been conducted, the author found that young people from GKPPD Mungkur still lack commitment to attending Bible study services, they still need support and encouragement and even good guidance from outside (external) in increasing their attendance at Bible study services. There are two internal factors (from within) and external factors (from outside) of the youth themselves. Internal factors include being busy (75%), waiting for friends' invitations (58%), not being confident/difficult to socialize (introvert) (0.8%), and also boredom/saturation (16%). External factors include distance (25%), family busyness (16%), leader/servant (51%), Science, Technology and Socialization (0.8%), not being on time (25%), and the last is because of less creative worship (16%). Based on the research results obtained by the researcher, it can be concluded that the most dominant factor that causes young people in GKPPD Mungkur to rarely attend Bible Study Services (PA) is due to busyness